2023
DOI: 10.3390/agronomy13061610
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Assimilation of the Guava (Psidium guajava) cv. Paluma under Different Pruning and Fruit Thinning Intensities

Adaniel Sousa dos Santos,
Gustavo Alves Pereira,
Wéverson Lima Fonseca
et al.

Abstract: In guava plants, production pruning can be performed twice a year, and the return of growth is dependent on the physiological responses that are altered by the different cultivation environments and adopted management. From this perspective, this study aimed to characterize the photosynthetic dynamics of guava plants influenced by different pruning and fruit thinning intensities during two growing seasons in the region of Currais, Piauí, Brazil. The plants were distributed in a randomized block design with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The increase in HI is influenced by an increase in NAR and CGR which is reflected through possitive correlation r= 0.622 and r= 0.284, respectively (Table 3). Food reserves produced through photosynthesis activity will influence the increase in assimilation which is translocated to the permanent sink, namely cucumber fruit (dos Santos et al, 2023;Wang et al, 2014). The results of this study showed that rice husk and cow manure produced higher HI compared to other organic ingredients.…”
Section: Resultsmentioning
confidence: 75%
“…The increase in HI is influenced by an increase in NAR and CGR which is reflected through possitive correlation r= 0.622 and r= 0.284, respectively (Table 3). Food reserves produced through photosynthesis activity will influence the increase in assimilation which is translocated to the permanent sink, namely cucumber fruit (dos Santos et al, 2023;Wang et al, 2014). The results of this study showed that rice husk and cow manure produced higher HI compared to other organic ingredients.…”
Section: Resultsmentioning
confidence: 75%
“…In tropical regions (e.g., Brazil), guava trees flower and fruit continuously throughout the year due to their wide edaphoclimatic adaptability [9]. However, the adoption of crop management techniques, such as pruning, has become essential for the commercial control of this species [10]. Pruning can maintain medium-sized plants and facilitate the management of crops, favoring and regulating fruit harvest [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the adoption of crop management techniques, such as pruning, has become essential for the commercial control of this species [10]. Pruning can maintain medium-sized plants and facilitate the management of crops, favoring and regulating fruit harvest [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations